The Role of KKN Students in the Rejuvenation of the Nurul Ulum Al-Husaeni Early Childhood Education Building as a Step to Support a Healthy Environment in Early Childhood (Case Study of Engineering Students at Mpu Tantular University KKN Year 2022, Al-Husaeni PAUD Sukasari Village/Subdistrict, Rumpin District, Bogor Regency/City, West Java Province) - Edison Hotaguan Manurung; Retno Indriyani Kusuma; Franka Hendra; Pahala Sinambela; Iqlima Tasya giana; Rony Alandry Davidson; Aldi Pratama Alya Saputra; Samotuho Ndruru; Agung Maulana Hidayat; Amarson Felix Silalahi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Early Childhood Education (PAUD) is the first and foremost foundation in the personal development of children, whether related to character, physical abilities, cognitive, language, arts, social, emotional, spiritual, self-discipline, self-concept, as well as independence and five senses. A child who has entered PAUD needs to be introduced to the concept of clean and healthy living behavior. Children need a sense of freedom, security, comfort, and stimulation to carry out activities in space. Activities carried out through the Real Work Lecture (KKN) program conducted by students of the Faculty of Engineering, University of Mpu Tantular with service methods such as educating early school children, as well as rejuvenating buildings at PAUD Al-Husaeni to create a safe, beautiful, and healthy for children